PAGELARAN WAYANG PURWA SEBAGAI MEDIA PENANAMAN NILAI RELIGIUS ISLAM PADA MASYARAKAT JAWA - Elly Herlyana (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2013)
Purwa Puppet is one form of Indonesian traditional classical cultures, which has evolved over the centuries. Puppet art show not only functions as a decorative art and an entertainment but also contains a lot of exemplary noble values. Puppet art show is a mirror of human life. Human dispositions are portrayed through puppets. This puppet art in its development also became an effective means of spreading Islam in Java in its early years. The puppet, strongly influenced by Hindu and animism, was modified in such a way by Wali Songo that it became a form of performance that was full of Islamic religious values. This paper aimed at determining the extent to which puppet performances can be used as a medium in conveying Islamic religious values in the archipelago in general, and in Java in particular.Keywords: puppets, values, Islam, Java